Molecular characteristics of Staphylococcus aureus strains isolated from subclinical mastitis of water buffaloes in Guangdong Province, China - Zhang, Dexian; Lu, Ximing; Feng, Xiangyan; Shang, Xuzeng; Liu, Qingyou; Zhang, Nan; Yang, Hong (Frontiers in Veterinary Science, 2023)
Intramammary infections (IMI) in animals reared for milk production can result in large economic losses and distress to the animals. Staphylococcus aureus is an important causative agent of IMI in dairy cows, but its prevalence in water buffaloes has not been determined. Therefore, the current study was conducted to investigate the prevalence of subclinical mastitis in water buffaloes and the antimicrobial susceptibility, virulence genes and biofilm formation abilities of S. aureus isolates recovered from water buffaloes in Guangdong, China. S. aureus strains were isolated from milk samples of water buffaloes with subclinical mastitis, and twofold microdilution, PCR and crystal violet staining methods were used to determine antimicrobial susceptibility, distributions of virulence and antimicrobial resistance genes and biofilm formation ability, respectively. Our results indicated that 29.44% of water buffaloes were diagnosed with subclinical mastitis, and the most prevalent pathogens were E. coli (96.17%), coagulase-negative staphylococci (CoNS) (67.60%) and S. aureus (28.57%). Most S. aureus isolates showed resistance to bacitracin, doxycycline, penicillin, florfenicol, and tetracycline but were susceptible to ciprofloxacin, ceftizoxime, cefoquinoxime and ofloxacin. Moreover, 63.72% of S. aureus isolates were positive for tetM, and the prevalence of msrB, blaZ, mecA, fexA, and tetK ranged from 21.24 to 6.19%. All S. aureus isolates harbored clfB and icaA genes, and the virulence genes hla (93.8%), hld (91.15%), clfA (90.27%), fnbA (86.73%), and hlb (83.19%), and tsst, icaD, sec, see, fnbB and sea showed a varied prevalence ranging from 3.5 to 65.49%. All S. aureus isolates possessed the ability to form biofilms, and 30.09% of isolates showed strong biofilm formation abilities, while 19.47% of isolates were weak biofilm producers. Our results indicated that subclinical mastitis is prevalent in water buffaloes in Guangdong, China, and S. aureus is prevalent in samples from water buffaloes with subclinical mastitis. Most S. aureus isolates were susceptible to cephalosporins and fluoroquinolones; thus, ceftizoxime and cefoquinoxime can be used to treat subclinical mastitis in water buffaloes.